2018
DOI: 10.1080/01443615.2018.1437717
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53, Bcl-2 and Bax in endometrial carcinoma, endometrial hyperplasia and normal endometrium: a histopathological study

Abstract: Our objective was to examine the expression rates of p53, Bcl-2 and Bax in endometrial carcinoma, endometrial hyperplasia and normal endometrium. A total of 94 endometrial frozen sections (carcinoma 48, hyperplasia 21, normal tissue 25) were examined immunohistochemically in terms of the expression rates of p53, Bcl-2 and Bax. All of the specimens in the non-malignant groups were positive for Bax, whereas this rate was 85.4% in the group with malignant specimens (p = .03). Conversely, p53 was expressed only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Bcl-2 is a potent inhibitor of apoptosis and increases proliferation ( 27 ). Furthermore, the Bcl-2/Bax ratio is the critical determinant for the induction or inhibition of apoptosis ( 28 ). PCNA is present in nuclei throughout the cell cycle and is synthesized in the late G 1 and S phases ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 is a potent inhibitor of apoptosis and increases proliferation ( 27 ). Furthermore, the Bcl-2/Bax ratio is the critical determinant for the induction or inhibition of apoptosis ( 28 ). PCNA is present in nuclei throughout the cell cycle and is synthesized in the late G 1 and S phases ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…To further verify the inhibitory effect of siASF1B on apoptosis, factors associated with apoptosis were investigated. Bax and p53 are pro-apoptotic genes, and Bcl-2 is an anti-apoptotic gene ( 41 , 42 ). Additionally, studies demonstrated that the activity of caspase-3 is strengthened during the process of cell apoptosis ( 43 - 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences indicate that mHtt induces cytotoxicity via enhancing oxidative stress and results in the activation of apoptotic signaling pathway (Nellemann et al, 2000;Pandey and Rajamma, 2018). The Bcl-2 family, which includes Bax and Bcl-2, plays a central role in the regulation of the mitochondria-mediated apoptosis (Wu et al, 2016;Mirakhor et al, 2018). Caspase 3 and caspase 9, downstream of the apoptotic signaling pathway, are proteolytic enzymes that function as key proteins to promote apoptosis (Wu et al, 2012a;Yao et al, 2017).…”
Section: Eb Enhances the Clearance Of Mhtt Via Atg7mentioning
confidence: 99%